HUBUNGAN BEBAN KERJA DAN MOTIVASI PERAWAT DENGAN KUALITAS DOKUMENTASI ASUHAN KEPERAWATAN - Osi Draini; Endah Ony Afiefi (Ensiklopedia Research and Community Service Review, 2026)
Nursing documentation is an important tool that can be used as an indicator of nursing care. Quality documentation functions as a means of communication among healthcare workers and as an evaluation tool for healthcare services, as well as an indicator of hospital quality. Incomplete and inaccurate documentation will impact patient safety and reduce the quality of service. The quality of documentation is influenced by various factors, including workload and nurse motivation. The purpose of this study is to determine the relationship between nurse workload and motivation with the quality of nursing care documentation. The research design used a quantitative study with a descriptive analytic method and a cross-sectional approach. The research location was conducted at X Hospital with sampling using the "total sampling" technique involving the entire population of nurses in the medical-surgical wards. The sample included 69 nurses from the total population. The data collection tool for this research used a questionnaire. The data in this study used the chi-square statistical test. The chi-square test results obtained a p-value of 0.025, smaller than the p-value of 0.05, which means there is a relationship between workload and the quality of nursing care documentation. The chi-square test results obtained a Fisher's exact value of 0.016, which means there is a relationship between nurse motivation and the quality of nursing care documentation. The suggestion of this study is expected to serve as an evaluation material for hospital management in improving the quality of nursing documentation. Keywords: Workload, Nurse Motivation, Documentation Quality, Nursing Care